2020
DOI: 10.1007/jhep01(2020)181
|View full text |Cite
|
Sign up to set email alerts
|

Two-colour QCD phases and the topology at low temperature and high density

Abstract: We delineate equilibrium phase structure and topological charge distribution of dense two-colour QCD at low temperature by using a lattice simulation with two-flavour Wilson fermions that has a chemical potential µ and a diquark source j incorporated. We systematically measure the diquark condensate, the Polyakov loop, the quark number density and the chiral condensate with improved accuracy and j → 0 extrapolation over earlier publications; the known qualitative features of the low temperature phase diagram, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 77 publications
(154 reference statements)
11
34
2
Order By: Relevance
“…To proceed we fit simultaneously our lattice data for the diquark condensate, the chiral condensate and the quark number density in the region aμ ∈ ð0; 0.12Þ by modified formulas 22 quite well, we conclude that at low density (μ < 540 MeV) the system under study is well described by ChPT. A similar conclusion was also drawn in papers [29,32,33].…”
Section: Fermionic Observablessupporting
confidence: 86%
See 1 more Smart Citation
“…To proceed we fit simultaneously our lattice data for the diquark condensate, the chiral condensate and the quark number density in the region aμ ∈ ð0; 0.12Þ by modified formulas 22 quite well, we conclude that at low density (μ < 540 MeV) the system under study is well described by ChPT. A similar conclusion was also drawn in papers [29,32,33].…”
Section: Fermionic Observablessupporting
confidence: 86%
“…The two-color QCD at finite chemical potential has been studied with lattice simulations quite intensively, see, e.g., [24][25][26][27][28][29][30][31][32][33][34][35] and references therein. Mostly, these papers are aiming at the study of the phase diagram of two-color QCD in the region of small and moderate baryon densities.…”
Section: Introductionmentioning
confidence: 99%
“…The system was found to be confined at low temperature, with deconfinement only setting in at much larger chemical potential [21]. Similar conclusions were found in [23]. It is also worth noting that a recent study of QCD with nonzero isospin chemical potential [5] found a phase diagram very similar to that of [8], namely a pion condensed phase at low T and large µ, with a critical temperature that is nearly independent of µ, and a deconfinement transition line that intersects with the pion condensation transition.…”
Section: Introductionmentioning
confidence: 59%
“…There remain significant uncertainties relating to the extrapolation to zero diquark source j, with our data unable to distinguish between a linear j-dependence and the nonanalytic behaviour expected at least in the vicinity of the onset transition. This may be mitigated by adopting the reweighting method introduced in [5] and implemented in the context of QC 2 D in [23]; this will be left for future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation